2017
DOI: 10.1016/j.celrep.2017.06.047
|View full text |Cite
|
Sign up to set email alerts
|

A PML/Slit Axis Controls Physiological Cell Migration and Cancer Invasion in the CNS

Abstract: Cell migration through the brain parenchyma underpins neurogenesis and glioblastoma (GBM) development. Since GBM cells and neuroblasts use the same migratory routes, mechanisms underlying migration during neurogenesis and brain cancer pathogenesis may be similar. Here, we identify a common pathway controlling cell migration in normal and neoplastic cells in the CNS. The nuclear scaffold protein promyelocytic leukemia (PML), a regulator of forebrain development, promotes neural progenitor/stem cell (NPC) and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 98 publications
(135 reference statements)
4
55
0
Order By: Relevance
“…In the present study, DNA methylation pattern of genes involved in several signalling pathways including axon guidance (SLIT1-ROBO2 signalling pathway) [18][19][20][21] and Hippo signalling pathway [22][23][24] contributing to brain development was found to be altered in hNPCs exposed to HG. The SLIT1-ROBO2 signalling pathway genes including SLIT1, and its effector genes ROBO2, SRGAP1 and CDC42, mediate diverse cellular processes such as proliferation, migration, neurogenesis and axon guidance, while Hippo signalling pathway effectors i.e., YAP and TAZ regulate cell proliferation, stemness, differentiation and organ size.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…In the present study, DNA methylation pattern of genes involved in several signalling pathways including axon guidance (SLIT1-ROBO2 signalling pathway) [18][19][20][21] and Hippo signalling pathway [22][23][24] contributing to brain development was found to be altered in hNPCs exposed to HG. The SLIT1-ROBO2 signalling pathway genes including SLIT1, and its effector genes ROBO2, SRGAP1 and CDC42, mediate diverse cellular processes such as proliferation, migration, neurogenesis and axon guidance, while Hippo signalling pathway effectors i.e., YAP and TAZ regulate cell proliferation, stemness, differentiation and organ size.…”
mentioning
confidence: 52%
“…This suggests that SLIT1-ROBO2 signalling pathway genes were perturbed via altered DNA methylation or SLIT1 downregulation or both in hNPCs exposed to HG. Furthermore, impaired proliferation in hNPCs exposed to HG 4 appears to be caused by the altered expression of SLIT-ROBO signalling genes which play important roles in proliferation, migration, and neurogenesis and axon guidance during brain development 18,20,21 . Additionally, Hippo signalling pathway genes, YAP/TAZ have been implicated in neural progenitor cell proliferation, differentiation and neural tube development 24,[51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…The verification by independent dataset proved that PML and EPB41 are indeed the key genes that affect the prognosis of OSA. The nuclear scaffold protein promyelocytic leukemia gene (PML) has a dual role in cancer: it can act as the downstream target of oncogenic RAS and it can promote tumorigenesis (31). PML is a pro-apoptosis gene that can be indirectly suppressed by cisplatin-based systemic chemotherapy in nonsmall cell lung carcinoma (32).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of spheroidal derivations in the growth dynamics in culture is believed to be the fundamental property of brain tumour stem cells (BTSC), which determines the initiation and proliferation of tumours in brain tissue (Laks et al, 2009) and is similar to the NSC/NPCs property to form the "neurospheres". It should be noted that the similarity of characteristics between the glioma cells and NSCs: a similar phenotype, proteome, secretome, comparable profile of receptor expression, adhesion molecules and identical targets of migration (Nakano, 2015;Yamamuro et al, 2015;Song et al, 2016;Amodeo et al, 2017;Garcia et al, 2017;Mehta & Lo Cascio, 2017;Qin et al, 2017) -is assumed as phylogenetic and it is suggested that brain tumours are derived from NSC/NPCs undergoing aberrant changes, -BTSCs (Kusne & Sanai, 2015;Stangeland et al, 2015;Zong et al, 2015;Ledur et al, 2016;Okawa et al, 2017). The content of BTSCs in glioma tissue enlarges proportionally with an increase in their malignancy, which is accompanied by raised expression levels of immunocytochemical markers of their stem phenotype (Bao et al, 2014;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%